Hemispheric black carbon increase after the 13th-century Māori arrival in New Zealand - McConnell, Joseph R; Chellman, Nathan J; Mulvaney, Robert; Eckhardt, Sabine; Stohl, Andreas; Plunkett, Gill; Kipfstuhl, Sepp; Freitag, Johannes; Isaksson, Elisabeth; Gleason, Kelly E; Brugger, Sandra O; McWethy, David B; et al. (Nature, 2021)
New Zealand was among the last habitable places on earth to be colonized by humans. Charcoal records indicate that wildfires were rare prior to colonization and widespread following the 13th- to 14th-century Māori settlement, but the precise timing and magnitude of associated biomass-burning emissions are unknown, as are effects on light-absorbing black carbon aerosol concentrations over the pristine Southern Ocean and Antarctica. Here we used an array of well-dated Antarctic ice-core records to show that while black carbon deposition rates were stable over continental Antarctica during the past two millennia, they were approximately threefold higher over the northern Antarctic Peninsula during the past 700 years. Aerosol modelling demonstrates that the observed deposition could result only from increased emissions poleward of 40° S—implicating fires in Tasmania, New Zealand and Patagonia—but only New Zealand palaeofire records indicate coincident increases. Rapid deposition increases started in 1297 (±30 s.d.) in the northern Antarctic Peninsula, consistent with the late 13th-century Māori settlement and New Zealand black carbon emissions of 36 (±21 2 s.d.) Gg y−1 during peak deposition in the 16th century. While charcoal and pollen records suggest earlier, climate-modulated burning in Tasmania and southern Patagonia, deposition in Antarctica shows that black carbon emissions from burning in New Zealand dwarfed other preindustrial emissions in these regions during the past 2,000 years, providing clear evidence of large-scale environmental effects associated with early human activities across the remote Southern Hemisphere.
Keywords: Antarktis; iskjerner; miljø; paleoklimatologi

Antarctic icebergs reorganize ocean circulation during Pleistocene glacials - Starr, Aidan; Hall, Ian R.; Barker, Stephen; Rackow, Thomas; Zhang, Xu; Hemming, Sidney R.; van der Lubbe, H. J. L.; Knorr, Gregor; Berke, Melissa A.; Bigg, Grant R.; Cartagena-Sierra, Alejandra; Jiménez-Espejo, Francisco J.; et al. (Nature, 2021)
The dominant feature of large-scale mass transfer in the modern ocean is the Atlantic meridional overturning circulation (AMOC). The geometry and vigour of this circulation influences global climate on various timescales. Palaeoceanographic evidence suggests that during glacial periods of the past 1.5 million years the AMOC had markedly different features from today1; in the Atlantic basin, deep waters of Southern Ocean origin increased in volume while above them the core of the North Atlantic Deep Water (NADW) shoaled2. An absence of evidence on the origin of this phenomenon means that the sequence of events leading to global glacial conditions remains unclear. Here we present multi-proxy evidence showing that northward shifts in Antarctic iceberg melt in the Indian–Atlantic Southern Ocean (0–50° E) systematically preceded deep-water mass reorganizations by one to two thousand years during Pleistocene-era glaciations. With the aid of iceberg-trajectory model experiments, we demonstrate that such a shift in iceberg trajectories during glacial periods can result in a considerable redistribution of freshwater in the Southern Ocean. We suggest that this, in concert with increased sea-ice cover, enabled positive buoyancy anomalies to ‘escape’ into the upper limb of the AMOC, providing a teleconnection between surface Southern Ocean conditions and the formation of NADW. The magnitude and pacing of this mechanism evolved substantially across the mid-Pleistocene transition, and the coeval increase in magnitude of the ‘southern escape’ and deep circulation perturbations implicate this mechanism as a key feedback in the transition to the ‘100-kyr world’, in which glacial–interglacial cycles occur at roughly 100,000-year periods.
Keywords: Sørishavet; havstrømmer; isfjell; paleoklimatologi; paleoseanografi